2023
DOI: 10.3389/fimmu.2023.1151527
|View full text |Cite
|
Sign up to set email alerts
|

Evolving approaches to profiling the microbiome in skin disease

Abstract: Despite its harsh and dry environment, human skin is home to diverse microbes, including bacteria, fungi, viruses, and microscopic mites. These microbes form communities that may exist at the skin surface, deeper skin layers, and within microhabitats such as the hair follicle and sweat glands, allowing complex interactions with the host immune system. Imbalances in the skin microbiome, known as dysbiosis, have been linked to various inflammatory skin disorders, including atopic dermatitis, acne, and psoriasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 149 publications
0
9
0
Order By: Relevance
“…Skin has extremely low microbial biomass due to its dry and nutrient-poor conditions ( 26 ); it has ~1/100th the biomass of stool samples ( 27 ). Low microbial biomass makes obtaining high read depth from amplicon sequencing challenging.…”
Section: Methodsmentioning
confidence: 99%
“…Skin has extremely low microbial biomass due to its dry and nutrient-poor conditions ( 26 ); it has ~1/100th the biomass of stool samples ( 27 ). Low microbial biomass makes obtaining high read depth from amplicon sequencing challenging.…”
Section: Methodsmentioning
confidence: 99%
“…The development of inflammatory acne lesions may result from a change from skin homeostasis to a state of inflammation [ 87 ], a process which is thought to involve: (i) excess sebum production, (ii) increased C. acnes presence and metabolic activity, leading to cytotoxic metabolite release in the pilosebaceous unit, (iii) pro-inflammatory cytokine release, (iv) recruitment of immune cells to the acne lesion locale, (v) incessant C. acnes pathogenic activity marked by biofilm formation and immune cell involvement, and (vi) an overall alteration to and dysbiosis of the skin flora in acne patients [ 14 , 15 , 87 , 92 , 93 ]. The succession of events outlined above remains a debated topic; for example, immune cells may first initiate hyperkeratinization and comedone formation [ 61 , 87 , 94 ].…”
Section: Review Of the Anti-inflammatory Properties Of Clindamycinmentioning
confidence: 99%
“…C. acnes is a known commensal bacterium on human skin, yet its involvement in the pathogenesis of acne has not been fully elucidated. Certain virulent and acne-causing strains of C. acnes are thought to be promoters of inflammation [ 10 , 14 , 15 , 92 ]. Building upon the idea that C. acnes activity within the pilosebaceous unit is central to inflammation in acne [ 90 ], it has been reported that the pilosebaceous unit is a hostile, oxygen-poor environment [ 92 ], but that C. acnes thrives in this environment by feeding on sebaceous lipids; thus, sebum quantity is likely directly related to C. acnes colonization on the skin and acne severity [ 61 ].…”
Section: Review Of the Anti-inflammatory Properties Of Clindamycinmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we recognized the challenges of low biomass even on skin lesions and attempted to sequence cDNA sequences of 16S amplicons instead of the corresponding DNA sequences directly. How this unique approach could have resulted in biased representations of certain Phyla has not been well characterized [41]. Future studies that collect detailed information on serial medications, may provide novel insights on the long-term trajectories of therapeutic effects on the lesional microbiota.…”
Section: Limitationsmentioning
confidence: 99%